Infusing high-impact practices in undergraduate public health curricula: Models, lessons learned, and administrative considerations from two public universities - Przybyla, Sarahmona M.; Cprek, Sarah E.; Kiviniemi, Marc T. (Frontiers in Public Health, 2022)
High-impact practices (HIPs) can improve the rigor, quality, and outcomes of undergraduate education. Several high-impact practices are explicitly woven into the overarching goals, learning objectives, and curricular competencies for undergraduate public health degree programs, while others are natural fits. However, capitalizing on the value of HIPs for public health undergraduates requires a conscious effort in the process of curriculum design, course delivery, and administration of these programs. In this paper, we discuss both conceptual approaches and practical steps involved in the integration of HIPs in curriculum design and implementation. We discuss two exemplars of undergraduate programs that incorporate high-impact practices, illustrating how the same practices can be developed and implemented in different but equally effective ways across programs. We close with practical suggestions for designing or refining an undergraduate program to maximize the inclusion and effectiveness of high-impact practices.